Subtract 1/2(z+4)−3(1/4z+1) . Use fractions in final form.

1 answer

To simplify this expression, we need to distribute and combine like terms. Let's start by distributing the 1/2 to (z + 4) and the -3 to (1/4z + 1):

1/2 * (z + 4) - 3 * (1/4z + 1)

= (1/2 * z) + (1/2 * 4) - (3 * 1/4 * z) - (3 * 1)

= (1/2z) + 2/2 - (3/4z) - 3

Now, let's combine the like terms:

= 1/2z + 2/2 - 3/4z - 3

= 1/2z - 3/4z + 2/2 - 3

To add or subtract fractions, we need a common denominator. In this case, the least common denominator (LCD) is 4. Let's rewrite the fractions with the common denominator:

= 2/4z - 3/4z + 2/2 - 3

Now, let's combine the like terms:

= (2 - 3)/4z + 2/2 - 3

= (-1)/4z + 1 - 3

= -1/4z - 2

Therefore, the final simplified form of 1/2(z + 4) - 3(1/4z + 1) is -1/4z - 2.